REHABILITASI MENTAL REMAJA PUTUS SEKOLAH DENGAN SOLUTION FOCUSED BRIEF THERAPY (SFBT) SEBAGAI INTERVENSI PSIKOLOGI DI PARE - Beti Malia Rahma Hidayati; Yasin Nur Falah; Sugianto (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
This service uses a problem-based approach that is considered effective for change, which is a research model by looking for something to be associated with the research process towards the process of social change. The purpose of this service is to 1. Analyze the mental condition of teenage dropouts who are members of The Kanisir in Kampung Baru, Lamong village, Badas sub-district, Kediri district. 2. Proving Solutive Focused Brief Therapy (SFBT) as a psychological intervention in rehabilitating the mentality of adolescents who drop out of school. 3. Assessing the achievement of change through Solutive Focused Brief Therapy (SFBT) as a psychological intervention in rehabilitating the mentality of adolescents who drop out of school. SFBT psychological intervention was conducted in 3 sessions with a duration of 60 minutes in each session. It is known that the psychological dynamics of the subject seen from the aspects of cognitive abilities, affective abilities, and conative abilities still have a dominant tendency to deficiencies or weaknesses. 2. It is known that the implementation of SFBT runs smoothly, the subject follows the stages well, starting from preparation, intervention, to the implementation of problem-free talk techniques, scaling questions techniques, exception seeking questions techniques, miracle questions techniques. 3. Solutive Focused Brief Therapy (SFBT) psychological intervention can be an effective method in helping adolescents discover their internal strengths, build hope, and develop strategies to achieve their goals.